Feeding of HIV-exposed children in a city in south of Brazil: family capability, clinical and social conditions - Marília Alessandra Bick; Paulo Sergio Ceretta; Cristiane Cardoso de Paula (Instituto Materno Infantil de Pernambuco, 2020)
Abstract Objectives: to evaluate the association between the sociodemographic and clinical aspects of the caregiver and the child, the family's ability to prepare and administer milk and complementary feeding of children exposed to HIV. Methods: cross-sectional study performed with 72 caregivers, in Brazil, through the tool of sociodemographic and clinical characterization of the caregiver and the Capability to Care for HIV-Exposed Children Assessment Scale. Results: there was a high capability to feed (76.6%), both for milk (85.0%) and comple-mentary (65%) feeding. For the milk feeding, accessing the health unit in any situation (p=0.003), having other child exposed to HIV (p=0.013), maintaining the follow-up in the health service (p=0.048) and not consuming alcohol (p=0.045) influenced on the higher probability of the caregiver to present high capability, while residing in the peri-urban area (p=0.002) indicated moderate capability. For the complementary feeding, the higher the schooling (p=0.025), the number of appointments scheduled for the child (p=0.045) and the child being followed up in the health service (p=0.035), the higher the probability of obtaining high capability. Conclusions: the exposure of social and clinical factors of caregivers influences the ability to feed. To ensure adequate nutrition, it is necessary for the health services to be able to consider the geo-socio-cultural characteristics of families in the elaboration of guidelines.